(untitled) (International Journal of Architecture and Urbanism, 2023)
This study focuses on the adaptive redesign of Lawang Sewu, a prominent landmark in Semarang, Indonesia. The building, constructed in the early 20th century, has witnessed historical events and changes throughout its existence. In recent years, there has been a growing interest in preserving and revitalizing Lawang Sewu as a cultural heritage site. However, the adaptive redesign is not without challenges, including structural instability, environmental degradation, functional obsolescence, aesthetic discordance, and social resistance. This research essay aims to explore the adaptive redesign of Lawang Sewu from various perspectives and propose strategies for achieving energy efficiency and sustainability objectives. The essay is organized into chapters that provide an overview, literature review, case study analysis, discussion of historical and socio-environmental aspects, examination of visual impact, and a conclusion. The study also discusses the concept of authenticity in heritage conservation and presents a design proposal for Lawang Sewu’s acoustic enhancement. The results of the case study analysis highlight the complexity of the adaptive redesign project and its cultural context and project site in Semarang.